2019
DOI: 10.3389/fmars.2018.00531
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal Energy Transfer and Organic Carbon Production at the Deep Seafloor

Abstract: Hydrothermal Energy and Organic Carbon oceanic ridge crests, volcanic arcs and back-arc systems are expected to significantly influence biomass production rates. A particular challenge is to develop observing strategies that will account for the full range of environmental variables while attempting to derive global or regional estimates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 248 publications
(455 reference statements)
1
39
0
Order By: Relevance
“…Total organic carbon (TOC) on exterior surfaces of inactive chimneys in the Mariana Trough may be up to five times the TOC on the exterior surface of active sulfides, consistent with high microbial productivity on inactive sulfides (Kato et al, 2010;Li et al, 2017). Despite this evidence, others posit that microbial activities are likely to be low (Le Bris et al, 2019). While the potential for microbial activity on metal sulfides is evident, metagenomic surveys and TOC measures are not sufficient tools to assess metabolic activity, including carbon fixation rates, on inactive sulfides (Olins et al, 2013;Le Bris et al, 2019).…”
Section: Microbial Diversity Abundance and Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Total organic carbon (TOC) on exterior surfaces of inactive chimneys in the Mariana Trough may be up to five times the TOC on the exterior surface of active sulfides, consistent with high microbial productivity on inactive sulfides (Kato et al, 2010;Li et al, 2017). Despite this evidence, others posit that microbial activities are likely to be low (Le Bris et al, 2019). While the potential for microbial activity on metal sulfides is evident, metagenomic surveys and TOC measures are not sufficient tools to assess metabolic activity, including carbon fixation rates, on inactive sulfides (Olins et al, 2013;Le Bris et al, 2019).…”
Section: Microbial Diversity Abundance and Activitymentioning
confidence: 99%
“…Despite this evidence, others posit that microbial activities are likely to be low (Le Bris et al, 2019). While the potential for microbial activity on metal sulfides is evident, metagenomic surveys and TOC measures are not sufficient tools to assess metabolic activity, including carbon fixation rates, on inactive sulfides (Olins et al, 2013;Le Bris et al, 2019). Experiments involving incubations at in situ temperatures, pressures, and mineralogical conditions, together with methods of measuring incorporation of labeled substrates, remain challenging to undertake in the deep sea.…”
Section: Microbial Diversity Abundance and Activitymentioning
confidence: 99%
“…The diverse communities in the relatively homogeneous and stable deep sea (Snelgrove and Smith 2002) largely depend on the supply of organic matter produced in shallower photosynthetically active waters (Ruhl and Smith 2004, Ruhl et al 2008). In this context, deep‐sea hydrothermal vents (HV) may be used as natural laboratories because they are hot spots of chemoautolithotrophic‐based primary productivity and biomass where productivity correlates, at least partially, with environmental stress (Johnson et al 1988, 1994, reviewed in Le Bris et al 2019). At HVs, oxygenated cold seawater percolates through and reacts with the ocean crust, forming oxygen‐depleted, acidic, and toxic vent fluids (reviewed in Le Bris et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In this context, deep‐sea hydrothermal vents (HV) may be used as natural laboratories because they are hot spots of chemoautolithotrophic‐based primary productivity and biomass where productivity correlates, at least partially, with environmental stress (Johnson et al 1988, 1994, reviewed in Le Bris et al 2019). At HVs, oxygenated cold seawater percolates through and reacts with the ocean crust, forming oxygen‐depleted, acidic, and toxic vent fluids (reviewed in Le Bris et al 2019). Their dilution with oxygenated water creates environments hosting microbial communities that obtain their energy through the oxidation of chemical compounds, which makes up the trophic basis of dense faunal assemblages (Sievert and Vetriani 2012).…”
Section: Introductionmentioning
confidence: 99%
“…At our current stage of knowledge, it remains difficult to compare senescent vents, where communities can rely on megafauna biomass previously produced by in situ chemosynthetic primary production, to old inactive vents. Old inactive vents, or hydrothermal sulfide deposits, can be tens of thousands years old and could also produce bacterial biomass by local chemosynthetic activity (Le Bris et al, 2019). To our knowledge, studies at older inactive vents considered only visually observed megafauna.…”
Section: Discussion Senescent Vents -A Species Rich Ecotonementioning
confidence: 99%